Mxene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst and its preparation method and application
The synthesis of MXene-supported Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst was solved by ultrasonic stirring, which solved the problems of insufficient activity of a single palladium catalyst and complex preparation process, achieved high electrocatalytic activity and stability, and reduced costs.
Patent Information
- Application Number
- CN202310037320.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-01-10
AI Technical Summary
The single palladium catalyst has limited active sites, poor particle aggregation and poor durability, resulting in a decrease in catalytic stability. The preparation process of MXene-based catalysts is cumbersome and costly.
Ultrasonic and stirring method were used to synthesize the hydrogen evolution electrocatalyst of MXene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst. The dispersion and dissolution of palladium sources, silver sources and MXene were promoted through the one-pot method, thereby improving the distribution uniformity of nanoparticles, reducing the content of precious metals Pd and improving the Catalytic activity.
High electrocatalytic activity and electrochemical stability are achieved, the use of Pd is reduced, the preparation process is simplified, the cost is reduced, and the utilization rate of the catalyst is improved.
Smart Images

Figure CN116145173B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of catalysts for electrolytic reactions, and in particular relates to a MXene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst and a preparation method and application thereof. Background Art
[0002] For a long time, hydrogen (H2) has been considered an ideal clean energy carrier because the product of hydrogen combustion is water, which does not cause environmental pollution and can be recycled. 70% of the earth is covered by oceans, and hydrogen separated from water is inexhaustible. Among various hydrogen production methods, the method of producing hydrogen by electrolysis of water is considered to be one of the effective ways to produce hydrogen on a large scale and sustainably.
[0003] Platinum (Pt) is considered to be the most effective material for electrocatalytic hydrogen evolution reaction due to its excellent hydrogen evolution performance, but its high cost and limited natural reserves seriously hinder its large-scale application. Compared with Pt, Pd-based electrocatalysts are more likely to achieve commercial industrial utilization due to their lower cost. Therefore, palladium (Pd) is generally considered to be one of the most suitable materials to replace Pt as an efficient catalyst. However, single Pd has limited active sites, poor particle aggregation and poor durability, which leads to a decrease in the active area of the catalyst and a decrease in catalytic stability, which seriously hinders its practical application in the field of catalytic reactions. To solve the above situation, introducing a second transition metal into Pd to form a bimetallic material is considered to be a promising strategy. By adjusting the electronic structure through the synergistic effect between the two elements, not only can the utilization rate of Pd be improved, but also the catalytic activity of Pd-based catalysts can be greatly improved. Compared with single metal nanoparticles, bimetallic nanoparticles have become a research hotspot due to their excellent electrochemical properties.
[0004] A novel electrocatalyst based on exfoliated two-dimensional (2D) MXene (Ti3C2Tx) loaded with Pt and Pd bimetallic oxide alloy nanoparticles (NPs) (composed of PtO a PdO bNPs@Ti3C2Tx) is synthesized by solution plasma (SP) modification. This composite catalyst shows high HER catalytic performance under alkaline conditions (Bingbing Cui, Bin Hu, Jiameng Liu, Minghua Wang, Yingpan Song, Kuan Tian, Zhihong Zhang, and Linghao He, ACS Appl. Mater. Interfaces. 2018, 10 (28): 23858-23873.). However, the preparation process of this MXene-supported HER nanocatalyst involves the surface modification and synthesis of MXene by solution plasma (SP), which makes the process of this MXene-supported HER nanocatalyst very cumbersome and costly. Summary of the invention
[0005] In order to solve the problems of limited single palladium active sites, poor particle aggregation, poor durability, decreased catalytic stability, and cumbersome preparation process and high cost of MXene-based catalysts. The present invention aims to provide a MXene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst and its preparation method and application. The mass percentage of the Pd precious metal in the catalyst is 3% to 9%. As a hydrogen evolution electrocatalyst, it has high electrocatalytic activity. The Pd-Ag bimetallic composite nanoparticles are uniformly loaded on the conductive substrate and have good crystallinity. Compared with the commercially available Pd / C electrocatalyst, the content of the precious metal Pd is reduced and has high electrocatalytic activity. The preparation method of the present invention is simple, and the ultrasonic and stirring treatment methods are combined to improve the utilization rate of Pd and greatly improve the catalytic activity of the Pd-based catalyst. Therefore, the purpose of the present invention is achieved through the following technical solutions.
[0006] The MXene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst provided by the present invention comprises: a conductive substrate and Pd-Ag bimetallic composite nanoparticles uniformly loaded on the conductive substrate, wherein the mass ratio of Pd nanoparticles to the conductive substrate in the Pd-Ag bimetallic composite nanoparticles is (0.04-0.1):1, the mass ratio of Ag nanoparticles to the conductive substrate in the Pd-Ag bimetallic composite nanoparticles is (0.05-0.07):1, the mass ratio of Pd nanoparticles to Ag nanoparticles in the Pd-Ag bimetallic composite nanoparticles is 1:(0.5-1.7), and the conductive substrate is MXene.
[0007] Furthermore, the MXene is Ti3C2.
[0008] Furthermore, the particle size of the Pd-Ag bimetallic composite nanoparticles is 8-13 nm, and the Pd-Ag bimetallic composite nanoparticles are uniformly dispersed on the conductive substrate.
[0009] Furthermore, the mass percentage of the noble metal palladium in the MXene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst is 3% to 9%.
[0010] Furthermore, the mass percentage of the noble metal palladium in the MXene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst is 9%.
[0011] The preparation method of the MXene-supported Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst provided by the present invention comprises the following steps:
[0012] (1) mixing a palladium source and hydrochloric acid and then sonicating to obtain a mixed solution 1;
[0013] (2) mixing the mixed solution 1 of step (1) with the silver source solution and then ultrasonicating the mixture to obtain a mixed solution 2;
[0014] (3) mixing the mixed solution 2 of step (2) with the MXene aqueous solution and then sonicating to obtain a mixed solution 3;
[0015] (4) mixing the reducing agent and purified water and then sonicating to obtain a mixed solution 4;
[0016] (5) adding the mixed solution 4 of step (4) to the mixed solution 3 of step (3) to obtain a reaction solution;
[0017] (6) After ultrasonicating the reaction solution in step (5) for a certain period of time, the solution is moved to a magnetic stirrer for stirring and reacting. After stirring and reacting, the solution is moved to a centrifuge tube for centrifugation and washing to obtain a Pd-Ag / MXene composite.
[0018] (7) Drying the Pd-Ag / MXene composite in step (6) in a vacuum drying oven to obtain the MXene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst.
[0019] Preferably, in step (1), the palladium source is palladium chloride, the ultrasonic time is 5 to 10 min; the concentration of the hydrochloric acid is 0.1 to 0.2 mol / L; and the ratio of the mass of the palladium source to the volume of the hydrochloric acid is 1 mg:(2.5-5) mL.
[0020] Preferably, in step (1), the ratio of the mass of the palladium source to the volume of hydrochloric acid is 1 mg:(3-5) mL.
[0021] Preferably, in step (1), the concentration of the hydrochloric acid is 0.2 mol / L.
[0022] Preferably, in step (1), 3.3-6.7 mg of palladium chloride and 20 mL of 0.2 mol / L hydrochloric acid are ultrasonically mixed for 5-10 min until the solution is uniformly mixed.
[0023] Preferably, the mass ratio of the palladium source in step (1) to the silver source in step (2) is 1:(0.3-2).
[0024] Preferably, the mass ratio of the palladium source in step (1) to the silver source in step (2) is 1:(0.5-2).
[0025] Preferably, the mass ratio of the palladium source in step (1) to the MXene in step (3) is (0.05-0.11):1.
[0026] Preferably, the mass ratio of the silver source in step (2) to the MXene in step (3) is (0.03-0.07):1.
[0027] Preferably, in step (2), the silver source solution is silver nitrate, the concentration of the silver source solution is 0.01 to 0.05 mol / L, and the ultrasonic time is 5 to 10 min.
[0028] Preferably, in step (2), the mixed solution 1 of step (1) and 0.24-0.47 mL of silver nitrate aqueous solution are ultrasonically treated for 5-10 min until the solution is uniformly mixed.
[0029] Preferably, in step (3), the MXene aqueous solution is a Ti3C2 aqueous solution, the concentration of the MXene aqueous solution is 5 to 10 mg / mL, and the ultrasonic time is 10 to 15 min.
[0030] Preferably, in step (3), the mixed solution 2 of step (2) and the MXene aqueous solution are ultrasonically treated for 10 to 15 minutes until the solutions are uniformly mixed.
[0031] Preferably, in step (4), the reducing agent is sodium borohydride, and the mass ratio of the reducing agent to the MXene in step (3) is (0.05-0.08):1; the pure water is laboratory distilled water, and the ultrasonic time is 5-10 min.
[0032] Preferably, in step (4), 5 mg of sodium borohydride and 10 mL of laboratory distilled water are ultrasonically mixed for 5 to 10 minutes until the solution is uniformly mixed.
[0033] Preferably, in steps (1)-(4), the power of the ultrasound is 600-800W.
[0034] Preferably, step (6) is carried out at 20-25°C.
[0035] Preferably, in step (6), the ultrasonic time is 0.5 to 2 h; the ultrasonic power is 600 to 800 W; the speed of the magnetic stirrer is 500 to 800 rpm / min; the stirring reaction time is 20 to 24 h; the centrifugal speed is 8000 to 11000 rpm; the centrifugal time is 8 to 12 min; and the washing is performed with anhydrous ethanol, and the centrifuge tube is 50 mL.
[0036] Preferably, in step (7), the temperature of the vacuum drying oven is 50-60° C. and the drying time is 8-12 hours.
[0037] Preferably, in step (7), the temperature of the vacuum drying oven is 50°C.
[0038] In the above scheme, it should be noted that the present invention adopts a one-pot method combined with ultrasonic treatment to synthesize MXene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst, which not only promotes the dispersion and dissolution of palladium source, silver source solution, and MXene, but also can further improve the distribution uniformity of nanoparticles, thereby improving the catalytic performance of the bimetallic composite hydrogen evolution catalyst.
[0039] The present invention also provides the use of the MXene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst in hydrogen evolution by electrolysis of water in a PEM (proton exchange membrane) electrolyzer.
[0040] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0041] 1. The MXene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst provided by the present invention has a relatively simple preparation method. The one-pot method combined with ultrasonic treatment can make the Pd-Ag bimetallic composite nanoparticles uniformly loaded on the conductive substrate, avoiding a large amount of agglomeration of the nanoparticles during the reaction, thereby increasing the electron transmission speed between the conductive substrate and the Pd-Ag bimetallic nanoparticles and improving their stability.
[0042] 2. The MXene-supported Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst provided by the present invention has good crystallinity and excellent electrochemical stability as a hydrogen evolution electrocatalyst. The mass percentage of the precious metal palladium in the obtained MXene-supported Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst is 3% to 9%. Compared with the commercially available Pd / C catalyst with a mass percentage of 10%, the content of the precious metal Pd is reduced, and it has a higher electrocatalytic activity, and can be widely used in the field of hydrogen evolution by electrolysis of water in PEM electrolyzers. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1This is the XRD (X-ray diffraction) spectrum of the Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst prepared in Examples 1-4.
[0044] Figure 2 TEM (transmission electron microscope) image of the Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst prepared in Examples 1-4.
[0045] Figure 3 HAADF-SEM and Mapping images of the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst prepared in Example 3.
[0046] Figure 4 HER (electrochemical hydrogen evolution reaction) curves comparing the Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst prepared in Examples 1-4 with a commercial Pd / C having a mass percentage of 10% in a 0.5M H2SO4 aqueous solution.
[0047] Figure 5 This is a stability test curve of the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst prepared in Example 3 in a 0.5M H2SO4 aqueous solution. DETAILED DESCRIPTION
[0048] The specific implementation of the present invention is further described below in conjunction with the examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.
[0049] Example 1
[0050] The Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst comprises the following steps:
[0051] Step 1: 3.3 mg of palladium chloride was mixed with 16 mL of a 0.2 mol / L hydrochloric acid solution, and then ultrasonicated at 600 W for 9 min until the mixture was uniformly mixed to obtain a mixed solution 1;
[0052] Step 2: Mix the mixed solution 1 of step 1 with 0.79 mL of a 0.05 mol / L silver nitrate aqueous solution, and then ultrasonicate at an ultrasonic power of 700 W for 8 min until the mixture is uniformly mixed to obtain a mixed solution 2;
[0053] Step 3: Mix the mixed solution 2 in step 2 with 12 mL of a Ti3C2 aqueous solution having a concentration of 5 mg / mL, and then ultrasonicate for 14 min at an ultrasonic power of 600 W until the mixture is uniformly mixed to obtain a mixed solution 3;
[0054] Step 4: 4 mg of sodium borohydride was mixed with 10 mL of laboratory distilled water and then ultrasonicated at an ultrasonic power of 800 W for 10 min until the mixture was uniformly mixed to obtain a mixed solution 4;
[0055] Step 5: adding the mixed solution 4 of step 4 to the mixed solution 3 of step 3 to obtain a reaction solution;
[0056] Step 6: At room temperature, the reaction solution in step 5 was ultrasonicated at an ultrasonic power of 750 W for 1 h, then moved to a magnetic stirrer and stirred at 800 rpm / min for 24 h, centrifuged at 8000 rpm for 12 min, and washed three times with ethanol to obtain a Pd-Ag / Ti3C2 composite.
[0057] Step 7: Dry the Pd-Ag / Ti3C2 composite obtained in step 6 in a vacuum drying oven at 60° C. for 8 h to obtain a Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst.
[0058] The XRD pattern of the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst obtained in Example 1 is as follows Figure 1 As shown, the characteristic peaks in the spectrum are consistent with the XRD standard spectrum of Pd (JCPDS: 46-1043), the XRD standard spectrum of Ag (JCPDS: 04-0783) and the purchased Ti3C2, indicating that a high-purity Pd-Ag / Ti3C2 composite is obtained.
[0059] TEM of the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst obtained in Example 1 is as follows Figure 2 As shown in a, Pd-Ag nanoparticles are uniformly loaded on the conductive substrate Ti3C2, and the particle size of the Pd-Ag nanoparticles is 11.5 nm.
[0060] Example 2
[0061] The Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst comprises the following steps:
[0062] Step 1: 5 mg of palladium chloride was mixed with 18 mL of a 0.15 mol / L hydrochloric acid solution, and then ultrasonicated at 600 W for 7 min until the mixture was uniformly mixed to obtain a mixed solution 1;
[0063] Step 2: Mix the mixed solution 1 of step 1 with 0.35 mL of a 0.05 mol / L silver nitrate aqueous solution, and then ultrasonicate at an ultrasonic power of 800 W for 5 min until the mixture is uniformly mixed to obtain a mixed solution 2;
[0064] Step 3: Mix the mixed solution 2 in step 2 with 12 mL of a Ti3C2 aqueous solution having a concentration of 5 mg / mL, and then ultrasonicate for 12 min at an ultrasonic power of 600 W until the mixture is uniformly mixed to obtain a mixed solution 3;
[0065] Step 4: 4 mg of sodium borohydride was mixed with 10 mL of laboratory distilled water and ultrasonicated at 700 W for 6 min until the mixture was uniformly mixed to obtain a mixed solution 4;
[0066] Step 5: adding the mixed solution 4 of step 4 to the mixed solution 3 of step 3 to obtain a reaction solution;
[0067] Step 6: At room temperature, the reaction solution in step 5 was ultrasonically treated at an ultrasonic power of 650 W for 0.8 h, then moved to a magnetic stirrer and stirred at a speed of 600 rpm / min for 20 h, centrifuged at a speed of 11,000 rpm / min for 8 minutes, and washed three times with ethanol to obtain a Pd-Ag / Ti3C2 composite.
[0068] Step 7: Dry the Pd-Ag / Ti3C2 composite obtained in step 6 in a vacuum drying oven at 55° C. for 10 h to obtain a Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst.
[0069] Example 2 The XRD pattern of the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst obtained is as follows Figure 1 As shown, the characteristic peaks in the spectrum are consistent with the XRD standard spectrum of Pd (JCPDS: 46-1043), the XRD standard spectrum of Ag (JCPDS: 04-0783) and the purchased Ti3C2, indicating that a high-purity Pd-Ag / Ti3C2 composite is obtained.
[0070] TEM of the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst obtained in Example 2 is as follows Figure 2 As shown in b, Pd-Ag nanoparticles are uniformly loaded on the conductive substrate Ti3C2, and the particle size of the Pd-Ag nanoparticles is 11 nm.
[0071] Example 3
[0072] The Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst comprises the following steps:
[0073] Step 1: 6.7 mg of palladium chloride was mixed with 20 mL of a 0.2 mol / L hydrochloric acid solution, and then ultrasonicated at 600 W for 10 min until the mixture was uniformly mixed to obtain a mixed solution 1;
[0074] Step 2: Mix the mixed solution 1 of step 1 with 0.6 mL of a 0.02 mol / L silver nitrate aqueous solution, and then ultrasonicate at an ultrasonic power of 600 W for 10 min until the mixture is uniformly mixed to obtain a mixed solution 2;
[0075] Step 3: Mix the mixed solution 2 in step 2 with 7.5 mL of an 8 mg / mL Ti3C2 aqueous solution, and then ultrasonicate for 15 min at an ultrasonic power of 700 W until the mixture is uniformly mixed to obtain a mixed solution 3;
[0076] Step 4: 5 mg of sodium borohydride was mixed with 10 mL of laboratory distilled water and ultrasonicated at 800 W for 9 min until the mixture was uniformly mixed to obtain a mixed solution 4;
[0077] Step 5: adding the mixed solution 4 of step 4 to the mixed solution 3 of step 3 to obtain a reaction solution;
[0078] Step 6: At room temperature, the reaction solution in step 5 was ultrasonicated at an ultrasonic power of 800 W for 2 h, then moved to a magnetic stirrer and stirred at 700 rpm / min for 21 h, centrifuged at 8500 rpm for 11 min, and washed three times with ethanol to obtain a Pd-Ag / Ti3C2 composite.
[0079] Step 7: Dry the Pd-Ag / Ti3C2 composite obtained in step 6 in a vacuum drying oven at 50° C. for 9 h to obtain a Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst.
[0080] Example 3 The XRD pattern of the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst obtained is as follows Figure 1 As shown, the characteristic peaks in the spectrum are consistent with the XRD standard spectrum of Pd (JCPDS: 46-1043), the XRD standard spectrum of Ag (JCPDS: 04-0783) and the purchased Ti3C2, indicating that a high-purity Pd-Ag / Ti3C2 composite is obtained.
[0081] TEM of the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst obtained in Example 3 Figure 2 As shown in c, Pd-Ag nanoparticles are uniformly loaded on the conductive substrate Ti3C2, and the particle size of the Pd-Ag nanoparticles is 8 nm.
[0082] HAADF-SEM and Mapping of the Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst obtained in Example 3 Figure 3 As shown, Pd, Ag, Ti, O and C elements are evenly distributed, proving that Pd-Ag nanoparticles are uniformly dispersed on Ti3C2.
[0083] The stability test curve of the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst obtained in Example 3 in a 0.5M H2SO4 aqueous solution is shown in FIG. Figure 5 As shown by Figure 5 It can be seen that the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst obtained in Example 3 has excellent electrocatalytic stability.
[0084] Example 4
[0085] The Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst comprises the following steps:
[0086] Step 1: 6 mg of palladium chloride was mixed with 15 mL of 0.1 mol / L hydrochloric acid, and then ultrasonicated at 700 W for 5 min until the mixture was uniformly mixed to obtain a mixed solution 1;
[0087] Step 2: Mix the mixed solution 1 of step 1 with 1.4 mL of a 0.01 mol / L silver nitrate aqueous solution, and then ultrasonicate for 6 min at an ultrasonic power of 700 W until the mixture is uniformly mixed to obtain a mixed solution 2;
[0088] Step 3: Mix the mixed solution 2 in step 2 with 6 mL of a Ti3C2 aqueous solution having a concentration of 10 mg / mL, and then ultrasonicate at an ultrasonic power of 600 W for 10 min until the mixture is uniformly mixed to obtain a mixed solution 3;
[0089] Step 4: Mix 3 mg of sodium borohydride with 10 mL of laboratory distilled water and ultrasonicate at 800 W for 5 min until the mixture is uniformly mixed to obtain a mixed solution 4;
[0090] Step 5: adding the mixed solution 4 of step 4 to the mixed solution 3 of step 3 to obtain a reaction solution;
[0091] Step 6: At room temperature, the reaction solution in step 5 was ultrasonically treated at an ultrasonic power of 600 W for 1.2 h, then moved to a magnetic stirrer and stirred at a speed of 500 rpm / min for 22 h, centrifuged at a speed of 9000 rpm / min for 10 minutes, and washed three times with ethanol to obtain a Pd-Ag / Ti3C2 composite.
[0092] Step 7: Dry the Pd-Ag / Ti3C2 composite obtained in step 6 in a vacuum drying oven at 50° C. for 12 hours to obtain a Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst. The Pd-Ag bimetallic composite nanoparticles are uniformly dispersed on the conductive substrate.
[0093] Example 4 The XRD pattern of the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst obtained is as follows Figure 1 As shown, the characteristic peaks in the spectrum are consistent with the XRD standard spectrum of Pd (JCPDS: 46-1043), the XRD standard spectrum of Ag (JCPDS: 04-0783) and the purchased Ti3C2, indicating that a high-purity Pd-Ag / Ti3C2 composite is obtained.
[0094] TEM of the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst obtained in Example 4 is as follows Figure 2 As shown in FIG. d, Pd-Ag nanoparticles are uniformly loaded on the conductive substrate Ti3C2, and the particle size of the Pd-Ag nanoparticles is 13 nm.
[0095] The element quantitative analysis of the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst obtained in Examples 1-4 is performed, and the test results are shown in Table 1.
[0096] Table 1
[0097]
[0098] From Table 1 of SEM element quantitative analysis, it can be seen that the mass ratio of Pd nanoparticles and conductive substrate is (0.04-0.1):1, the mass ratio of Ag nanoparticles and conductive substrate is (0.05-0.07):1, the mass ratio of Pd nanoparticles and Ag nanoparticles is 1:(0.5-1.7), and the mass of Pd accounts for 3% to 9% of the mass of Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst.
[0099] The HER curves of the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst obtained in Examples 1 to 4 and the commercially available Pd / C catalyst with a mass percentage of 10% in a 0.5M H2SO4 aqueous solution are shown in FIG. Figure 4 As shown by Figure 4 It can be seen that the Ti3C2 loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalysts obtained in Examples 1 to 4 have good electrocatalytic hydrogen evolution performance compared with the commercially available Pd / C catalyst. -2The overpotentials required for the Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalysts obtained in Examples 1 to 4 are all lower than those required for the commercially available Pd / C catalyst, wherein the overpotentials required for the Ti3C2-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalysts obtained in Examples 1 to 4 are 126 mV, 103 mV, 77 mV, and 87 mV, respectively, and the overpotential required for the commercially available Pd / C catalyst is 142 mV.
[0100] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. MXene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst, characterized in that: include: A conductive substrate and Pd-Ag bimetallic composite nanoparticles uniformly loaded on the conductive substrate, wherein the mass ratio of Pd nanoparticles to the conductive substrate in the Pd-Ag bimetallic composite nanoparticles is (0.04-0.1):1, the mass ratio of Ag nanoparticles to the conductive substrate in the Pd-Ag bimetallic composite nanoparticles is (0.05-0.07):1, the mass ratio of Pd nanoparticles to Ag nanoparticles in the Pd-Ag bimetallic composite nanoparticles is 1:(0.5-1.7), and the conductive substrate is MXene; the particle size of the Pd-Ag bimetallic composite nanoparticles is 8-13 nm, and the Pd-Ag bimetallic composite nanoparticles are uniformly dispersed on the conductive substrate; The preparation of the MXene-supported Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst comprises the following steps: (1) mixing a palladium source and hydrochloric acid and then sonicating to obtain a mixed solution 1; the palladium source is palladium chloride, the sonication time is 5 to 10 minutes, the concentration of the hydrochloric acid is 0.1 to 0.2 mol / L, and the ratio of the mass of the palladium source to the volume of the hydrochloric acid is 1 mg: (2.5-5) mL; (2) Mixing the mixed solution 1 of step (1) with a silver source solution and then ultrasonicating to obtain a mixed solution 2; the silver source solution is silver nitrate, the concentration of the silver source solution is 0.01-0.05 mol / L, and the ultrasonication time is 5-10 min; the mass ratio of the palladium source in step (1) to the silver source in step (2) is 1:(0.3-2); (3) Mixing the mixed solution 2 of step (2) with the MXene solution and then ultrasonicating to obtain a mixed solution 3; the mass ratio of the palladium source in step (1) to the MXene in step (3) is (0.05-0.11):1; the MXene solution is a Ti3C2 solution, the concentration of the MXene solution is 5-10 mg / mL, and the ultrasonication time is 10-15 min; the mass ratio of the silver source in step (2) to the MXene in step (3) is (0.03-0.07):1; (4) Mixing the reducing agent and water and then sonicating to obtain a mixed solution 4; the reducing agent is sodium borohydride, the mass ratio of the reducing agent to the MXene in step (3) is (0.05-0.08):1, and the sonication time is 5-10 min; (5) adding the mixed solution 4 of step (4) to the mixed solution 3 of step (3) to obtain a reaction solution; (6) subjecting the reaction solution of step (5) to ultrasonic treatment, stirring for reaction, centrifuging after stirring for reaction, and washing to obtain a Pd-Ag / MXene composite; (7) Drying the Pd-Ag / MXene composite of step (6) to obtain the MXene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst.
2. The MXene-supported Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst according to claim 1, characterized in that: The ultrasonic time in step (6) is 0.5 to 2 hours; the speed of the stirring reaction in step (6) is 500 to 800 rpm / min; the stirring reaction time in step (6) is 20 to 24 hours; and the drying in step (7) is drying in a vacuum drying oven at 50 to 60° C. for 8 to 12 hours.
3. Application of the MXene-loaded Pd-Ag bimetallic composite nanoparticle hydrogen evolution electrocatalyst according to claim 1 in hydrogen evolution by water electrolysis in a PEM electrolyzer.
Citation Information
Patent Citations
Method for visible light catalytic dehydrogenation of formic acid with Ag-Pd nanosheet catalyst
CN110508313A
Preparation method of hydrogen evolution catalyst of three-dimensional MXene-based carrier
CN111744519A